Landmark Base Point Approach to Positional and Coastal Accuracy Analysis for Historical Map Before WWI: A Case Study 1836 Moltke and 1914 German Blue about in Historical Peninsula of İstanbul - Şahin, Cumhur; Ergün, Bahadır; Bilucan, Furkan (Springer Heidelberg, 2025)
Cartography, unquestionably one of the world's oldest disciplines of scientific study, is among the fields that have been most influenced by technological improvements. These improvements have enhanced interest in historical maps while also paving the way for modern mapping. All of this process has created new topics of study for cartographers. It is possible to examine old maps using software such as MapAnalyst which can enable the investigation of time-dependent changes. In this study, two historical maps, namely, Moltke and German Blue, were analyzed in the study area including the Historical Peninsula, Golden Horn, some part of Bosphorus, and the Marmara Sea in & Idot;stanbul, T & uuml;rkiye, employing Helmert, Affine, and Huber loss robust estimation methods. It was revealed that the region with the highest deterioration on both maps is between Be & scedil;ikta & scedil; and & Uuml;sk & uuml;dar. The coastline change analysis was also performed. According to the results, it was observed that the regions with the most coastal change are located on the southern and eastern coasts of the Historical Peninsula.
Keywords: Moltke map; German Blue map; & Idot;stanbul historical peninsula; Helmert; Affine; Huber loss